O pojęciach i praktyce kłamstwa w epoce nowoczesnej - Dietzsch, Steffen (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2019)
Lies occupy a surprisingly favorable place within our daily life. As the Polish aphorist Stanisław Jerzy Lec once remarked: if you want to see the lie you need to face the obvious truth. With lies, we do not simply stigmatize the dark part or the „backside” of the humankind. To lie, meaning the ability to deceive, with or without words, even to deceive with the truth (for example in sta-tistics), is one of the intellectual modalities of human existence, as well as an expression of misery. This leads to the paradox: One cannot live with lies or, at the same time, live without them. Lies thus reveal their double nature; they attempt to maintain viv-id things, just as they generally tend to destroy them. This dou-ble nature of lies makes it impossible to condemn them by means of „ethical conviction”, as Max Weber would put it, or with the words of another famous French philosopher of our present time, Vladimir Jankélévitch, who says that consciousness is already provided with an inner disposition to lie, as a litmus test of its noble and mean sides.
Concepts of lies and lie practices in the modern era
Keywords: lie; double nature; modernity; Plato; Kant; Nietzsche; Scheler; Jankélévitch; politics; love; ressentiment